Análise de textos didáticos de matemática: Um mapeamento e uma proposta metodológica fundada numa perspectiva hermenêutica - De Oliveira, Fábio Donizeti [UNESP] (My University, 2010)
This article discusses some methodological possibilities for analyzing textbooks in Mathematics Education. Its starting point was a review - which allowed us to build a general map - of the production developed by consolidated Research Groups that deal with this theme in Brazil. This map allowed us to propose a complementary/alternative guide to analyse textbooks according to a hermeneutical approach.
Analysis of math textbooks: Surveying researches to build a methodological proposal according to a hermeneutical approach
Keywords: Mathematics Education; Methodology; Textbooks